Inequality in Financial Inclusion and Income Inequality - Aslan, Goksu (IMF Working Papers; Working Paper, 2017)
We investigate the link between gender inequality in financial inclusion and income inequality, with three contributions to the recent literature. First, using a micro-dataset covering 146,000 individuals in over 140 countries, we construct novel, synthetic indices of the intensity of financial inclusion at the individual and country level. Second, we derive the distribution of individual financial access 'scores' across countries to document a 'Kuznets'-curve in financial inclusion. Third, cross-country regressions confirm that our measure of inequality in financial access is significantly related to income inequality, above and beyond other factors previously highlighted in the literature.